Effect of Biochar Application in Combination with Different Nutrient Sources on Cauliflower Production at Kaski Nepal - Timilsina, S.; Khanal, A.; Vista, S.P.; Poon, T.B. (Journal of Agriculture and Environment, 2021)
Field experiments were conducted during the winter season of 2016/17 and 2017/18 to assess the effect of biochar application in combination with different nutrient sources on cauliflower (Brassica oleraceae var. botrytis) production in sandy loam soil. The experiment was conducted using a Randomized Complete Block Design (RCBD) with ten different treatment viz., Farmer’s practice as control treatment, Recommended dose of fertilizer (200:120:80 kg NPK/ha), Composted biochar @ 1t/ha, Urine Soaked biochar @ 1t/ha, Mineral fertilizer (200:120:80 kg NPK/ha) mixed biochar @ 1t/ha, Humic acid soaked biochar @ 1 t/ha, Composted biochar @ 2t/ha, Urine Soaked biochar @ 2t/ha, Mineral fertilizer (200:120:80 kg NPK/ha) mixed biochar @ 2t/ha and Humic acid soaked biochar @ 2 t/ha, each replicated for three times. The application of biochar in combination with mineral fertilizers significantly increased the yields of cauliflower in both consecutive years. Application of biochar @ 2 t/ha along with mineral fertilizer at recommended dose increased curd yield of cauliflower by 37 % compared to that of only mineral fertilizer application and by 59 % compared to that of control treatment. Biochar and inorganic sources of nutrition together in soil showed superiority over other practices and would be of immense value to increase the productivity of cauliflower.